Tribological (wear) properties of aluminum–silicon eutectic base alloy under dry sliding condition - Alias, Tuti Yasmin; Khalid, Asad A.; Haque, Md. Mohafizul (Elsevier, 2004)
Low expansion, low density and high resistance to corrosion at ambient temperature make the aluminum–silicon alloys very suitable for wear resistance components in the automotive industry. In this study, wear behaviors of both the as-cast and heat-treated Al–Si alloy have been investigated. The cylindrical shaped wear testing specimens were prepared from cast ingot and some of the specimens were then heat-treated according to ASTM standard. Wear experiments on both samples were conducted with a pin-on-disk type wear testing apparatus. The test variables were the rotational speed, input weight, and time/sliding distance. The extent of wear damage was estimated by means of weight loss technique. The full heat-treatment has shown a great influence on the wear properties of the aluminum–silicon piston alloy. In general, the increase in wear with an increase in speed, input load and sliding distance was observed for both as-cast and heat-treated specimens.